2002
DOI: 10.1007/3-540-45708-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Essential Algebraic Structure within the AES

Abstract: Abstract. One difficulty in the cryptanalysis of the Advanced Encryption Standard AES is the tension between operations in the two fields GF (2 8 ) and GF (2). This paper outlines a new approach that avoids this conflict. We define a new block cipher, the BES, that uses only simple algebraic operations in GF ( 2 8 ). Yet the AES can be regarded as being identical to the BES with a restricted message space and key space, thus enabling the AES to be realised solely using simple algebraic operations in one field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 13 publications
3
139
0
Order By: Relevance
“…Furthermore, not every property of the embedded cipher is of immediate relevance to the original cipher. Indeed, an example of a weakness of the larger algebraically embedded cipher that does not translate to the original cipher was given in [12]. However our framework allows us to immediately identify some embeddings that inevitably have little cryptanalytical value.…”
Section: Natural Extensions Of Embeddingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, not every property of the embedded cipher is of immediate relevance to the original cipher. Indeed, an example of a weakness of the larger algebraically embedded cipher that does not translate to the original cipher was given in [12]. However our framework allows us to immediately identify some embeddings that inevitably have little cryptanalytical value.…”
Section: Natural Extensions Of Embeddingsmentioning
confidence: 99%
“…The embedding of the AES in a larger cipher called Big Encryption System (BES) was introduced in [12]. The main goal of this construction was to represent the AES within a framework where the cipher could be expressed through simple operations (inversion and affine transformation) in the field F = GF (2 8 ).…”
Section: The Bes Extension Of the Aesmentioning
confidence: 99%
See 2 more Smart Citations
“…The first algebraic attack on a block cipher was discussed in [18]. For recent developments in the area of algebraic attacks on block ciphers see [1,2,5,6,15,16]. In [6] Courtois and Pieprzyk showed that AES [8] can be attacked by solving an overdefined system of algebraic equations.…”
Section: Introductionmentioning
confidence: 99%